Knowledge work in the age of control: capitalising on human capital - Benda Hofmeyr (Acta Academica, 2022)
The main claim that I aim to substantiate in this article is that power in the form of control is exerted in a more insidious manner now that knowledge work has become ‘networked’. To this end, I first describe societal control in the current epoch. Given the fact that my focus is on knowledge work, I next revisit the human capital literature with the aim of coming to a more precise understanding of what knowledge work is. The literature on “leveraging human capital” (Burud and Tumolo 2004) evidences how human capital theory draws on the conditions of free-floating control to optimally capitalise on knowledge workers. Models of overt management have come to be replaced by more expansive and insidious models of control that extend beyond the sphere of work into the intimate recesses of private life. Control operative at the societal level (Castells 1996) extends beyond the macro-level (neoliberal), to the meso-level (organisational), and the micro-level (self-governance). Next, I critically consider the implications of these conditions of control for the (self-)governance of the knowledge worker by drawing on Han’s (2017) further specification of control as “smart power”. I come to the conclusion that under the conditions of apparently greater autonomy and discretion that is so pervasive in the management literature discussing knowledge workers, governance as “control” induces constant work erasing the boundaries between work and private life. Neoliberalism with its mantra of investment in human capital has succeeded in producing an optimally efficient, ever-working subject. Throughout my analyses are informed by Foucault’s (2008) concept of “governmentality”, which fuses the presiding rationality (knowledge) with governance (power as control) to throw light on how human conduct is being conducted (orchestrated) for optimal efficiency.